Sanksi Adat Pertarungan Di Desa Huta Pasir Kecamatan Simangambat Kabupaten Padang Lawas Utara - Hsb, Mara Ongku (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2023)
The role of custom in society becomes an unwritten law, customary law is usually considered as law that arises from the community because it originates from habit, apart from that customary law is also considered (living law) but if the reality is carefully examined then from the point of view of customary law will be known. which living customary law can be observed from everyday behavior, which living customary law can be observed from everyday behavior. This research method is qualitative to explore experiences and the opinion of key informants about the customary sanction of engagement in Huta Pasir village, Simangambat sub district, North Padang Lawas district. Research study approach field using observation and interviews. The results of the research in the village of Huta Pasir, Simangambat district customary sanctions are considered as laws that apply in the community and are followed by other communities, one of which is about the customary sanctions of engagement, the sanction is that if both parties violate the customary promise, they both pay the loss of one another. twice as much as bolina , a kind of dowry given by men to women.